Designing Supercapacitor from Nanocarbon Materials - Mohd Abid, Mohd Asyadi Azam; Abdul Manaf, Nor Syafira; raja seman, raja noor amalina (2014)
In this project, we focus on the fabrication of energy device, namely, supercapacitor by using an equal weight ratio of nanocarbons as electrode material. Supercapacitor works as energy storage due to its high power density and excellent cycling stability. This work covers the effect of various compositions of carbon nanotube, graphene, and activated carbon in different electrolytes. Electrolytes are presented by lithium ion electrolyte and also aqueous solutions like sulfuric acid and potassium hydroxide. Electrochemical performance including capacitance from cyclic voltammetry and charge/discharge analysis will be provided to determine the suitability of the supercapacitor towards potential commercialization.